South Asian-Canadian Gay Men and HIV: Social, Cultural, and Psychological Factors That Promote Health - Durrani, Samir; Sinacore, Ada L. (Canadian Journal of Counselling and Psychotherapy, 2016)
The extant literature on HIV prevention for gay men in Canada does not focus on differences based on race and ethnicity; consequently, few studies have explored how the intersections of race, ethnicity, and sexual identity influence risk for HIV infection. The purpose of this study was to address this gap in the literature by interviewing 4 South Asian-Canadian gay men about their experiences with HIV risk and prevention. A hermeneutic phenomenological approach was used to identify the social, cultural, and psychological factors that increase risk for HIV infection, as well as the factors that promote wellness for these men. Implications for research and counselling practice with this community are discussed.